2008
DOI: 10.2169/internalmedicine.47.0429
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective and Randomized Study for Improvement of Acute Asthma by Non-invasive Positive Pressure Ventilation (NPPV)

Abstract: Objective We hypothesized that non-invasive positive pressure ventilation (NPPV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
3
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 36 publications
4
50
3
5
Order By: Relevance
“…The first study 62 showed improved flow and fewer hospitalizations with NIV, versus sham NIV. The second study 63 reported similar conclusions with high inflation pressure, but not with low pressure or with standard medical therapy. In patients with severe acute asthma, the addition of NIV to standard therapy probably accelerates the improvement in lung function, decreases the inhaled bronchodilator requirement, and shortens the stay in the ICU.…”
Section: Asthmamentioning
confidence: 65%
“…The first study 62 showed improved flow and fewer hospitalizations with NIV, versus sham NIV. The second study 63 reported similar conclusions with high inflation pressure, but not with low pressure or with standard medical therapy. In patients with severe acute asthma, the addition of NIV to standard therapy probably accelerates the improvement in lung function, decreases the inhaled bronchodilator requirement, and shortens the stay in the ICU.…”
Section: Asthmamentioning
confidence: 65%
“…However, there was a more rapid improvement in the forced expiratory volume in the first second ( paring two pressure levels of noninvasive positive-pressure ventilation with oxygen therapy alone, a greater reduction in dyspnea and a greater increase in FEV 1 were reported for the group that received noninvasive ventilation. 36 Importantly, the patients in the latter two RCTs did not have severe exacerbation of asthma (none required endotracheal intubation). Overall, the quality and quantity of the evidence were low, and there were very few outcome events in any of the studies.…”
Section: Exacerbation Of Asthmamentioning
confidence: 97%
“…[34][35][36] One trial, which cited selection bias in patient enrolment leading to a small sample size (n = 35), found no differences in outcomes. 34 The second trial was a single-centre trial of 33 patients that used sham noninvasive ventilation in the control group.…”
Section: Exacerbation Of Asthmamentioning
confidence: 99%
“…1 Noninvasive ventilation (NIV) is commonly employed to reduce work of breathing and minimize respiratory discomfort in those patients whose exacerbations increase the work of breathing. [2][3][4][5] Many pa-tients requiring NIV may benefit from effective inhaled medication delivery. 6,7 Many factors influence the efficacy of aerosol delivery during NIV, such as ventilator type, ventilation mode, circuits, gas density, humidity, interfaces, aerosol generator type, particle size, aerosol generator position, and factors related to the patient (including type and severity of disease, respiratory pattern, and ability to tolerate a face mask).…”
Section: Introductionmentioning
confidence: 99%